The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2019
DOI: 10.1177/1548512919844021
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of Structure from Motion for reconnaissance augmentation and bandwidth usage reduction

Abstract: Modern militaries rely upon remote image sensors for real-time intelligence. A typical remote system consists of an unmanned aerial vehicle, or UAV, with an attached camera. A video stream is sent from the UAV, through a bandwidth-constrained satellite connection, to an intelligence processing unit. In this research, an upgrade to this remote-video-stream method of collection is proposed. A set of synthetic images of a scene captured by an UAV in a virtual environment is sent to a pipeline of computer vision a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
10
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
2
1

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(11 citation statements)
references
References 23 publications
1
10
0
Order By: Relevance
“…This paper is a direct continuation of work performed by Roeber et al 3 who demonstrated the use of SfM as a method of data compression for aerial imagery. Roeber's results were extremely promising, showing a compression of nearly 60% compared to the original set of imagery.…”
Section: Related Workmentioning
confidence: 63%
See 2 more Smart Citations
“…This paper is a direct continuation of work performed by Roeber et al 3 who demonstrated the use of SfM as a method of data compression for aerial imagery. Roeber's results were extremely promising, showing a compression of nearly 60% compared to the original set of imagery.…”
Section: Related Workmentioning
confidence: 63%
“…Building from recent research on this same topic using Structure from Motion (SfM), 3 which demonstrated 49%-60% compression from the original imagery, we propose a new SfM variant that is both faster and more spatially accurate than traditional methods, and most importantly, capable of calculating imagery replacements in real-time at 4 Hz on our test laptop.…”
Section: Application Of Real-time Structure From Motionmentioning
confidence: 99%
See 1 more Smart Citation
“…32 The engine has been used successfully for testing stereo computer vision techniques in simulation for automated aerial refueling applications 33 and for testing structure from motion. [34][35][36]…”
Section: Related Workmentioning
confidence: 99%
“…The virtual environment was built using the AftrBurner engine, a cross-platform visualization engine 32 . The engine has been used successfully for testing stereo computer vision techniques in simulation for automated aerial refueling applications 33 and for testing structure from motion [34][35][36] .…”
Section: Related Workmentioning
confidence: 99%